The Influence of Artificial Intelligence (AI), Information Technology Capabilities, and Employee Training on Accounting Process Efficiency at Public Accounting Firms in Ambon City - Silooy, Marissa (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI), information technology capabilities, and employee training on the efficiency of accounting processes in Public Accounting Firms (KAP) in Ambon City. This study uses a quantitative method with a survey approach on a population consisting of accounting staff in several Public Accounting Firms (KAP) in Ambon City. The results show that Artificial Intelligence (AI) and information technology capabilities significantly improve accounting process efficiency through task automation and better data management. Employee training also contributes significantly to ensuring the optimal utilization of new technologies. This study provides practical recommendations for Public Accounting Firms (KAP) to increase technology adoption and employee training to achieve higher efficiency in accounting processes.